Biliscrotum and Retroperitoneal Biloma: Spontaneous Rupture of the Biliary System presenting as an Incarcerated Inguinal Hernia - Brady, RRW (The Ulster Medical Society, 2006)
Spontaneous rupture of the biliary system is a well documented condition in infants1 but is rare in adults.2 We report the case of a 73-year-old gentleman who presented with clinical signs and symptoms mimicking that of a strangulated right inguinal hernia. At emergency operation the scrotum was found to contain bile. Following radiological imaging and exploratory surgery, a large retroperitoneal biloma was found. We discuss the clinical signs associated with biliscrotum and retroperitoneal biloma and describe our operative management of this patient. We review the previously reported cases of these rare clinical entities. We found that our case exhibited similarities in terms of the age of presentation and presence of distal common bile duct stones. This is, to our knowledge, the only reported case of a patient presenting with biliscrotum secondary to the assumed spontaneous rupture of the common bile duct and development of a retroperitoneal biloma.